Apparent tunneling barrier height and local work function of atomic arrays - Noei, Neda; Weismann, Alexander; Berndt, Richard (Beilstein Journal of Nanotechnology, 2018)
Spatially resolved measurements of the apparent tunneling barrier height Φapp in scanning tunneling microscopy have been used to estimate variations of the local work function Φ of surface structures. We experimentally show that Φapp can fail as a measure of Φ. The discrepancies are attributed to a kinetic-energy contribution to Φapp. This contribution depends on the lateral extent of the tunneling current filament and, consequently, on the local surface structure.
Keywords: scanning tunneling microscopy; tunneling barrier height; work function